An Accurate Real-Time Method for Face Mask Detection using CNN and SVM - Shili Hechmi (Universitas Negeri Malang, 2022)
Infectious respiratory diseases, including COVID-19, pose a significant challenge to humanity and a potential threat to life due to their severity and rapid spread. Using a surgical mask is among the most significant safety precautions that can help keep this sort of pandemic from spreading, and manual monitoring of large crowds in public places for face masks is problematic. In this research, we suggest a real-time approach for face mask detection. First, we use a multi-scale deep neural network to extract features. As a result, the attributes are better suited for training the detection system. We employ SVM post-processing in the classification stage to make the face mask detection method more robust. According to the experimental findings, our strategy considerably decreased the percentage of false positives and undetected cases.